A relação família e escola no processo educacional de estudantes com Transtorno do Espectro Autista (TEA) em aulas de matemática - SILVA, Karina Sousa da (2020)
This qualitative research aims to investigate the relationship between family and school in relation to the educational inclusion process of students with Autistic Spectrum Disorder (ASD) and their contributions to the academic and social development of these students. The research was conducted in a school of the municipal school system of the city of Belém-Pará, with two subjects: a representative of the family (mother) and the school (teacher) of a student with ASD. Data production occurred through a semi-structured interview with the participants. The results show the absence of dialogue between family and school regarding the teaching and learning process of the student with ASD, as well as the lack of understanding about Autistic Spectrum Disorder, which can hinder the development of the student with ASD and its inclusion in the school space. An effective relationship between family and school is considered fundamental in the context of basic education for an inclusive education.